Advancements in Fluid Power Technology: Sustainability, Electrification, and Digitalization (Springer Nature, 2025)
This open access book contains contributions from the Global Fluid Power Society (GFPS) PhD Symposium 2024. It reflects the collaborative efforts of researchers who are dedicated to pushing the boundaries of fluid power research. The GFPS PhD symposium, established in 2016 as a biannual event, is a platform for exchanging ideas and insights related to fluid power technology, among young researchers. It serves as a focal point for the exploration of various technical topics related to fluid power, including components, systems, and applications. Fluid power technology undergoes a rapid transformation towards electrification and digitalization, requiring innovation and new technical solutions across the industry, in response to societal requirements on different aspects of sustainability. The book covers a range of topics that align with the symposium's theme: Advancements in Fluid Power Technology: Sustainability, Electrification, and Digitalization. The content encompasses a wide spectrum of subjects, including fluid power applications, control and automation, energy efficiency, electrification, and environmental sustainability. The book can be a valuable reference for researchers and professionals interested in fluid power research and allied fields.